Pacifier disinfection procedure: superficial morphological aspects and microorganisms colonization - Renata Cristiane da SILVA; Denise Madalena Palomari SPOLIDORIO; Ângela Cristina Cilense ZUANON; Ricardo Henrique Moreton GODOI (Revista Sul-Brasileira de Odontologia, 2009)
Introduction and Objective: Evaluate superficial changes as well as the presence of C. albicans and S. mutans on latex and silicone pacifiers. Material and Methods: after thermal treatment and disinfection, forty latex and silicone pacifiers fragments were contaminated and submitted to boiling water during 5 and 10 minutes and microwave energy during 5 minutes. Results: Scanning Electron Microscopy revealed the greatest superficial alterations on latex samples compared to silicone. In despite of thermal treatment, none sample revealed the occurrence of S. mutans and C. albicans. Conclusion: Silicone pacifiers and the microwave energy showed to be the most appropriate and effective domestic procedure for disinfections of pacifiers.